1999
DOI: 10.1093/brain/122.11.2101
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cerebral structure in juvenile myoclonic epilepsy demonstrated with voxel-based analysis of MRI

Abstract: MRI scans of patients with idiopathic generalized epilepsy (IGE) are normal on visual assessment. Using an interactive anatomical segmentation technique and volume-of-interest measurements of MRI, we showed recently that patients with IGE had significantly larger cortical grey matter than control subjects. Further, 40% of individual patients with juvenile myoclonic epilepsy (JME), a syndrome of IGE in adolescence, had significant abnormalities of cerebral structure. In this study, we applied the automated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
233
3
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(264 citation statements)
references
References 26 publications
16
233
3
12
Order By: Relevance
“…For example, an increase in volume has been found in the medial frontal cortex of patients with JME,11, 28 whereas another study of JME patients found a decrease in a similar region 8. In addition, medial frontal gyrus was found to have decreased gray matter volume in groups of patients with GTCSO 10, 23.…”
Section: Discussionmentioning
confidence: 97%
“…For example, an increase in volume has been found in the medial frontal cortex of patients with JME,11, 28 whereas another study of JME patients found a decrease in a similar region 8. In addition, medial frontal gyrus was found to have decreased gray matter volume in groups of patients with GTCSO 10, 23.…”
Section: Discussionmentioning
confidence: 97%
“…VBM has been cross-validated with region-of-interest measurements and functional data in a number of studies (Vargha-Khadem et al, 1998;May et al, 1999;Woermann et al, 1999). This method is based on highresolution structural three-dimensional magnetic resonance images, registered in standard space, and is designed to find significant regional differences throughout the brain by applying voxelwise statistics within the context of Gaussian random fields (Ashburner and Friston, 2000).…”
Section: Vbm Protocolmentioning
confidence: 99%
“…This may support the studies with neuropsychological tests and advanced structural neuroimaging techniques showing focal cortical abnormalities mainly associated with frontal lobe in patients with JME. [17][18][19][20][21][22][23] Results of ours and similar studies seem to be challenging for further trials designed with tasks more spesific to the critical regions of cortical network.…”
mentioning
confidence: 99%